Differences in risk and costs between prehospital identified low-risk men and women with chest pain - Roland R J van Kimmenade; Niels van Royen; Eddy M M Adang; Goaris W A Aarts; Cyril Camaro; Martijn Rutten; Marc E R Gomes; Gilbert E Cramer; Peter Damman; Robert-Jan M Van Geuns; Laura Rodwell; Roger van Hout; et al. (Open Heart, 2023)
Objective Prehospital rule-out of non-ST-segment elevation acute coronary syndrome (NSTE-ACS) in low-risk patient with a point-of-care troponin measurement reduces healthcare costs with similar safety to standard transfer to the hospital. Risk stratification is performed identical for men and women, despite important differences in clinical presentation, risk factors and age between men and women with NSTE-ACS. Our aim was to compare safety and healthcare costs between men and women in prehospital identified low-risk patients with suspected NSTE-ACS.Methods In the Acute Rule-out of non-ST-segment elevation acute coronary syndrome in the (pre)hospital setting by HEART (History, ECG, Age, Risk factors and Troponin) score assessment and a single poInt of CAre troponin randomised trial, the HEAR (History, ECG, Age and Risk factors) score was assessed by ambulance paramedics in suspected NSTE-ACS patients. Low-risk patients (HEAR score ≤3) were included. In this substudy, men and women were compared. Primary endpoint was 30-day major adverse cardiac events (MACE), secondary endpoints were 30-day healthcare costs and the scores for the HEAR score components.Results A total of 863 patients were included, of which 495 (57.4%) were women. Follow-up was completed in all patients. In the total population, MACE occurred in 6.8% of the men and 1.6% of the women (risk ratio (RR) 4.2 (95% CI 1.9 to 9.2, p<0.001)). In patients with ruled-out ACS (97% of the total population), MACE occurred in 1.4% of the men and in 0.2% of the women (RR 7.0 (95% CI 2.0 to 14.2, p<0.001). Mean healthcare costs were €504.55 (95% CI €242.22 to €766.87, p<0.001) higher in men, mainly related to MACE.Conclusions In a prehospital population of low-risk suspected NSTE-ACS patients, 30-day incidence of MACE and MACE-related healthcare costs were significantly higher in men than in women.Trial registration number NCT05466591.